Editorial Note - Fisgativa , Carlos Mario (Disertaciones, 2024)
With the publication of this issue, Disertaciones magazine reaches 14 years of editorial activity as an open access digital journal. It constitutes a contribution of the Philosophy Program of the University of Quindío to the dissemination of knowledge and the philosophical activity from Colombia. There are 19 editions and more than 100 articles that have been published, which constitutes a valuable archive generated by this editorial exercise, which we hope will gain greater relevance, given the context of dispute about the need to democratize access to information and the results of research processes. For which the open access journal system (Open Journal Systems) is a reliable tool.